Communication Strategy of the Padang City Tourism Office in Building a Creative Village - Umi Chalzhum Caniago (Journal of Media and Communication | E-ISSN : 3063-9581, 2024)
Communication strategies are needed to produce a communication process that can be understood by the recipient of information in achieving goals. Therefore, the organization / or company must develop the right communication strategy so that the message conveyed to the target object can be understood properly. research was conducted to analyze the performance of the Tourism Office in implementing the strategy of the Creative Village, especially in the aspect of communication, because there are still many villages that do not participate in the activities of the Creative Village, this is due to the lack of understanding of the Village community about what, the purpose, the why and the elements of the Creative Village itself. Therefore, the thesis that the researcher made was entitled "Communication Strategy of the Tourism Office in Building Creative Villages". The purpose of the research is to find out the communication strategy of the Padang City Tourism Office, as well as to find out the supporting and inhibiting factors in implementing this communication strategy. The research method used is qualitative with a descriptive approach, types of field research and data collection techniques by conducting participatory observations, interviews, and documentation. The results of the research on the communication strategy of the Padang City Tourism Office Using the stages of communication strategy, namely: 1. Getting to know the audience, 2. Compiling messages, 3. Methods used, 4. Selection and use of media. This is also inseparable from the existence of supporting and inhibiting factors. And after the results of the research on the communication strategy of the Padang City Tourism Office in building a Creative Village has been carried out well, it's just that there are still some village people in Padang City District who do not understand what the Village is about, the purpose, why and the elements of the Creative Village so they choose not to participate in the Creative Village activities.